How do you solve \[{{x}^{2}}=-5x-5\]?
Answer
Verified
435.6k+ views
Hint: First take all the terms to the L.H.S and then compare the given quadratic equation with the general form given as: - \[a{{x}^{2}}+bx+c=0\]. Find the respective values of a, b and c. Now, find the discriminant of the given quadratic equation by using the formula: - \[D={{b}^{2}}-4ac\], where ‘D’ is the notation for the discriminant. Now, apply the formula: - \[x=\dfrac{-b\pm \sqrt{D}}{2a}\] and substitute the required values to get the answer.
Complete step by step solution:
Here, we have been provided with a quadratic equation: - \[{{x}^{2}}=-5x-5\] and we are asked to solve it. That means we have to find the values of x. So, let us apply the discriminant method to solve the given quadratic equation.
Now, taking all the terms to the L.H.S, we get,
\[\Rightarrow {{x}^{2}}+5x+5=0\]
Now, comparing the general form of a quadratic equation: - \[a{{x}^{2}}+bx+c=0\] with the given equation: - \[{{x}^{2}}+5x+5=0\], we can conclude that, we have,
$\Rightarrow $ a = 1, b = 5 and c = 5.
Applying the formula for discriminant of a quadratic equation given as: - \[D={{b}^{2}}-4ac\], where ‘D’ is the discriminant, we get,
\[\begin{align}
& \Rightarrow D={{5}^{2}}-4\times 1\times 5 \\
& \Rightarrow D=25-20 \\
& \Rightarrow D=5 \\
\end{align}\]
Now, we know that the solution of a quadratic equation in terms of its discriminant value is given as: -
\[\Rightarrow x=\dfrac{-b\pm \sqrt{D}}{2a}\]
So, substituting the given values and obtained values of D, we get,
\[\begin{align}
& \Rightarrow x=\dfrac{-5\pm \sqrt{5}}{2\times 1} \\
& \Rightarrow x=\dfrac{-5\pm \sqrt{5}}{2} \\
\end{align}\]
(i) Considering (+) sign we have,
\[\Rightarrow x=\dfrac{-5+\sqrt{5}}{2}\]
(ii) Considering (-) sign we have,
\[\Rightarrow x=\dfrac{-5-\sqrt{5}}{2}\]
Hence, the above two values of x are the roots or solution of the given quadratic equation.
Note:
One may note that here it will be difficult to use the middle term split method to solve the question. This is because it will be difficult for us to think of the factors like: \[\left( x-\left( \dfrac{-5+\sqrt{5}}{2} \right) \right)\] and \[\left( x-\left( \dfrac{-5-\sqrt{5}}{2} \right) \right)\]. You may apply the third method known as completing the square method to solve the question. In this method we have to convert the equation \[a{{x}^{2}}+bx+c=0\] into the form: - \[{{\left( x+\dfrac{b}{2a} \right)}^{2}}=\dfrac{D}{4{{a}^{2}}}\] and then by taking the square root we need to solve for the value of x. Remember that the discriminant formula is derived from completing the square method. You must remember the discriminant formula to solve the above question.
Complete step by step solution:
Here, we have been provided with a quadratic equation: - \[{{x}^{2}}=-5x-5\] and we are asked to solve it. That means we have to find the values of x. So, let us apply the discriminant method to solve the given quadratic equation.
Now, taking all the terms to the L.H.S, we get,
\[\Rightarrow {{x}^{2}}+5x+5=0\]
Now, comparing the general form of a quadratic equation: - \[a{{x}^{2}}+bx+c=0\] with the given equation: - \[{{x}^{2}}+5x+5=0\], we can conclude that, we have,
$\Rightarrow $ a = 1, b = 5 and c = 5.
Applying the formula for discriminant of a quadratic equation given as: - \[D={{b}^{2}}-4ac\], where ‘D’ is the discriminant, we get,
\[\begin{align}
& \Rightarrow D={{5}^{2}}-4\times 1\times 5 \\
& \Rightarrow D=25-20 \\
& \Rightarrow D=5 \\
\end{align}\]
Now, we know that the solution of a quadratic equation in terms of its discriminant value is given as: -
\[\Rightarrow x=\dfrac{-b\pm \sqrt{D}}{2a}\]
So, substituting the given values and obtained values of D, we get,
\[\begin{align}
& \Rightarrow x=\dfrac{-5\pm \sqrt{5}}{2\times 1} \\
& \Rightarrow x=\dfrac{-5\pm \sqrt{5}}{2} \\
\end{align}\]
(i) Considering (+) sign we have,
\[\Rightarrow x=\dfrac{-5+\sqrt{5}}{2}\]
(ii) Considering (-) sign we have,
\[\Rightarrow x=\dfrac{-5-\sqrt{5}}{2}\]
Hence, the above two values of x are the roots or solution of the given quadratic equation.
Note:
One may note that here it will be difficult to use the middle term split method to solve the question. This is because it will be difficult for us to think of the factors like: \[\left( x-\left( \dfrac{-5+\sqrt{5}}{2} \right) \right)\] and \[\left( x-\left( \dfrac{-5-\sqrt{5}}{2} \right) \right)\]. You may apply the third method known as completing the square method to solve the question. In this method we have to convert the equation \[a{{x}^{2}}+bx+c=0\] into the form: - \[{{\left( x+\dfrac{b}{2a} \right)}^{2}}=\dfrac{D}{4{{a}^{2}}}\] and then by taking the square root we need to solve for the value of x. Remember that the discriminant formula is derived from completing the square method. You must remember the discriminant formula to solve the above question.
Recently Updated Pages
Master Class 11 English: Engaging Questions & Answers for Success
Master Class 11 Computer Science: Engaging Questions & Answers for Success
Master Class 11 Maths: Engaging Questions & Answers for Success
Master Class 11 Social Science: Engaging Questions & Answers for Success
Master Class 11 Economics: Engaging Questions & Answers for Success
Master Class 11 Business Studies: Engaging Questions & Answers for Success
Trending doubts
10 examples of friction in our daily life
What problem did Carter face when he reached the mummy class 11 english CBSE
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
State and prove Bernoullis theorem class 11 physics CBSE
The sequence of spore production in Puccinia wheat class 11 biology CBSE